Effectiveness and Potential of E- Commerce in Rural area of Sonipat: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
E-commerce is increasingly playing a significant role in India's economy. This essay aims todemonstrate the current state trend of e-commerce in India's rural areas. Information for this study wasgathered from secondary sources, such as articles, journals, books, newspapers, etc., that were written inthe relevant fields. The study looks at the rising investment in rural e-commerce and how consumers canbenefit from online shopping by having access to more options, reduced prices, and time savings. Onlinebusinesses use computer networks internet to manage the buying and selling of labor goods.Thisessay makes an effort to highlight the numerous challenges faced by E-trade in India, appreciate theessential development components required for E-business, and convey the country's prosperity retailE-Commerce commerce. Digital progress is evident in the rise in internet mobile users, but it is unclearhow the government online merchants will turn this into productive internet utilization that boosts theeconomy. A few suggestions were made in this research study to address the problems, challenges, andbarriers to the growth development of e-commerce in rural and distant areas.